2020
DOI: 10.26740/ipf.v9n3.p459-465
|View full text |Cite
|
Sign up to set email alerts
|

The Validity and Reliability of Five-Tier Conception Diagnostic Test for Vector Concepts

Mirza Qonita,
Frida Ulfah Ermawati

Abstract: Abstract Misconceptions has commonly found in Physics concepts, including in Vector concepts. For example, students assumed when an object moves at a certain path and returns to the original position using different path, the displacement is not zero. Meanwhile, according to the Vector concept, the object displacement is zero when it moves and returns to the original position. This discrepancy is called misconception. Such misconception needs to be identified. One of them is by multi-tiers conception dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Therefore, the five-tier multiple choice instrument The parabolic motion produced in this study is valid, so it is feasible to use it to assess the concept understanding of SMA/MA students. The research result was in line with research conducted by [23] who also developed a five-tier multiple choice instrument on vector. The research result shown that the instrument developed is externally valid and reliable.…”
Section: Figure 3 Validity Assessment Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Therefore, the five-tier multiple choice instrument The parabolic motion produced in this study is valid, so it is feasible to use it to assess the concept understanding of SMA/MA students. The research result was in line with research conducted by [23] who also developed a five-tier multiple choice instrument on vector. The research result shown that the instrument developed is externally valid and reliable.…”
Section: Figure 3 Validity Assessment Resultssupporting
confidence: 86%
“…Because the four-tier multiple choice instrument is limited to the reasons for choosing the answer, It is important to create a five-tier system that includes confirmation of student answers in the shape of picture commands, equations, and also conclusions [22]. Currently, many fivetier multiple choice instruments have been developed in learning of physics, one of which is done by [23], which results in a five-tier multiple choice instrument on vector. Through the five-tier, it is possible to assess the understanding of the concept more [24].…”
Section: Introductionmentioning
confidence: 99%
“…Diagnostic tests determine weaknesses in students' understanding of a concept (Anam, 2019;Prodjosantoso, 2019). An excellent diagnostic test can provide an accurate picture of the misconceptions experienced by students based on the error information they make (Bayuni, 2018;Maharani, 2019;Qonita & Ermawati, 2020). Good diagnostic questions not only show that students do not understand certain parts of the material but can also show how students think in answering the questions given, even though the answers are not correct (Setiawan, 2020;Sari, 2020;Timothy, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The third and fourth-tiers, contain the respondent's reasons/arguments for the answers given in tier-2 and the respondent's beliefs on the choice of these reasons/arguments. The fifth tier is the respondent's open answer, and it can be in the form of a figure or statement that supports the answer in each tier, as well as a form of expression of knowledge and confirmation of the respondent (Qonita & Ermawati, 2020).…”
Section: Introductionmentioning
confidence: 99%